Comparison of Microstructure and Mechanical Properties of Induction and Vacuume Brazed Joint of Titanium Via Copper and Ag-Cu Eutectic Filler Metal / Mikrostruktura I Właściwości Mechaniczne Połączeń Tytanu Lutowanych Indukcyjnie I Próżniowo Z Użyciem Spoiwa Miedzianego I Eutektycznego Ag-Cu - Różański M.; Majewski D.; Krasnowski K. (Archives of Metallurgy and Materials, 2015)
This study presents the basic physico-chemical properties and describes the brazeability of titanium. The work contains the results of macro and microscopic metallographic examination as well as the results of strength-related tests of vacuum and induction brazed joints made of Grade 2 technical titanium using the Cu 0.99 and Ag 272 filler metal interlayers and F60T flux intended for titanium brazing in the air atmosphere.